(untitled) (Journal of Environmental Microbiology and Toxicology, 2021)
This study was designed to investigate the effects of Juglan nigra lectin on haematological parameters and lethal dose of rats. An authenticated Juglan nigra (UBHP401) collected from Lokoja was used to extract lectin and treated on Swiss Wistar rats (n=35) and (n=17) with weights from 75-129g for haematological parameters and LD50 respectively. The Wistar rats were divided into five equal groups labeled A, B, C, D, and E. Lectin concentrations were prepared and administered at stipulated days. Group A served as control, group B received 30%, C received 50%, D received 70% and group E received 90% of lectin intraperitoneally. Samples (Baseline-BL, First Harvests-FH and Second Harvest-SH) were collected from all the groups and analyzed for the following haematological parameters: white blood count (WBC), Red Blood count (RBC), Haemoglobin (HB), packed cell volume (PCV), platelet count, neutrophil, lymphocyte, monocytes, eosinophil and basophil. The data were analysed using two-way analysis of variance (ANOVA) in graph pad prism version 5.03. The Eosinophil count and white blood cell count were significantly increased P<0.005 and 0.05, whereas the HB, PCV and RBC showed significant different P<0.05 based on the day of exposure of the animal to the lectin, the platelet count was significantly increased on the basis of days of exposure of P<0.05, Eosinophil significantly increased too. Juglan nigra, (Nigerian walnut) Lectin is nontoxic as noted from LD50 result. Nigerian walnut lectin has a positive effect in haematopoietic activity of Swiss Wistar rats.